PENGARUH PEMAHAMAN REVOLUSI INDUSTRI 4.0 TERHADAP AKUNTANSI - Agustina, Theresia; Dermawan, Elizabeth Sugiarto (Jurnal Paradigma Akuntansi, 2024)
This study aims to detemine the effect of understanding the 4.0 Industrial Revolution in the use of Artificial Intelligence on Accounting. Knowing the effect of Big Data on Accounting, Knowing the effect of Cloud Computing on Accounting. This study uses data from 30 respondencets who are accountants who understand the Industrial Revolution 4.0 and who work woth IT or Big Data. The results show that Artifical Intelligence has a positive effect on accounting, Big Data has a positive effect on Accounting, Cloud computing has a positive effect on Accounting.